Do Impairments in Visual Functions Affect Skiing Performance? - Stalin, Amritha; Creese, Marieke; Dalton, Kristine Nicole (Frontiers in Neuroscience, 2021)
Nordic and alpine skiing related visual tasks such as identifying hill contours, slope characteristics, and snow conditions increase demands on contrast processing and other visual functions. Prospective observational studies were conducted to assess the relationships between skiing performance and a broad range of visual functions in nordic and alpine skiers with vision impairments. The study hypothesized that contrast sensitivity (CS), visual acuity (VA), and visual field (VF) would be predictive of skiing performance. Binocular static VA, CS, light sensitivity, glare sensitivity, glare recovery, dynamic VA, translational and radial motion perception, and VF were assessed in elite Para nordic (n=26) and Para alpine (n=15) skiers. Skiing performance was assessed based on skiers' raw race times. Performance on the visual function tests were compared with skiing performances using Kendall's correlations (with and without Bonferroni-Holm corrections) and linear multivariable regressions (p<0.05 considered significant). None of the vision variables were significantly correlated with performance in Para nordic or Para alpine skiing after Bonferroni-Holm corrections were applied. Before applying the corrections, VF extent (ρ= -0.37, p= 0.011) and static VA (ρ=0.26, p=0.066) demonstrated the strongest correlations with Para nordic skiing performance; in Para alpine skiing, static VA and CS demonstrated the strongest correlations with downhill (Static VA: ρ=0.54, p=0.046, CS: ρ=-0.50, p=0.06), super G (Static VA: ρ=0.50, p=0.007, CS: ρ=-0.51, p=0.017) and giant slalom (Static VA: ρ=0.57, p=0.01, CS: ρ=-0.46, p=0.017) performance. Dynamic VA and VF were significantly associated with downhill (ρ=0.593, p=0.04) and slalom (ρ=-0.49, p = 0.013). performances. Static VA was a significant predictor of giant slalom [(F(3,11)=24.71, p<0.001), R of 0.87], super G [(F(3,9)=17.34, p=0.002), R of 0.85], and slalom [(F(3,11)=11.8, p=0.002), R of 0.80] performance, but CS and VF were not. Interestingly, static VA and CS were highly correlated in both Para nordic (ρ=-0.60, p<0.001) and Para alpine (ρ=-0.80, p<0.001) skiers. Of the vision variables, only static VA and VF were associated with skiing performance and should be included as the in Para nordic and Para alpine classifications. The strong correlations between static VA and CS in these skiers with vision impairment may have masked relationships between CS and skiing performance.